2013
DOI: 10.7769/gesec.v4i3.270
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Administrative Professional in the Management of Complex Projects

Abstract: RESUMOComo uma profissão do tempo dos escribas, o secretariado se desenvolveu significativamente ao longo do tempo, contudo a pesquisa nesse campo parece não ter acompanhado o papel dos praticantes. Atualmente a especialização requerida do profissional de secretariado envolve não somente as habilidades que anteriormente caracterizavam seu trabalho mas também um conjunto de novas habilidades mais relacionadas com a administração da organização. Essas podem incluir mas não se limitam à viabilização de resultados… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…With respect to contextual skills of the project team, the results showed that the ES has yet to become better acquainted with these skills, corroborating the literature (Piscopo & Silveira, 2013). On the one hand, the general view of the ES, not being specialists in PM, were not expected to be perceived as having these skills.…”
Section: Discussion Of Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…With respect to contextual skills of the project team, the results showed that the ES has yet to become better acquainted with these skills, corroborating the literature (Piscopo & Silveira, 2013). On the one hand, the general view of the ES, not being specialists in PM, were not expected to be perceived as having these skills.…”
Section: Discussion Of Resultssupporting
confidence: 82%
“…We identified the following activities carried out by ES in PM, according to the perception of the project manager: teamwork, communication on multiple levels, problem solving, and people management. Corroborating the literature, communication is a strong competence of the ES (Piscopo & Silveira, 2013), and at the same time is one of the most cited reasons for failure in PM (Kerzner, 2017;Vezzoni et al, 2013). The activities related to the technical and contextual skills, although also identified as performed by the ES, showed a need to be better developed by the ES.…”
Section: Final Thoughtsmentioning
confidence: 95%
See 2 more Smart Citations
“…The secretariat provides support for the implementation of transparency, managing other initiatives quickly and effectively, deepening partnerships, and establishing new collaborations where necessary. Over time, the role of the secretariat in organizational capacity development has evolved from an administrative function to a strategic function (Ege, 2017;Trim, 2020;Hickmann et al, 2019;Bieńkowska, 2016;Mahoney & Deckop, 1986;Piscopo, M. R., & Silveira, F. F., 2013).…”
Section: Secretariat and Organizational Capacity Developmentmentioning
confidence: 99%